Far Eastern entomologist Sergey Yu. Storozhenko: almost 50 years of his scientific work in insects - Gorochov, Andrei V.; Lelej, Arkady S.; Proshchalykin, Maxim Yu.; Loktionov, Valery M.; Kuprin, Alexandr V. (Zootaxa, 2025)
Sergey Yuryevich Storozhenko was born on November 14, 1955 in the Soviet Union (USSR), in the town of Uzlovaya, Tula Region (currently Russia). He spent his childhood on Sakhalin Island, and then the family moved to the city of Khabarovsk, and later to the town of Ussuriysk, where his father headed the Department of Crop Production of the Primorsky Agricultural Institute. Sergey graduated from high school in 1973 in Ussuriysk. He received his higher education in Vladivostok, at the Far Eastern State University, the Faculty of Biology and Soils from which he graduated in 1978. In 1982, under the scientific supervision of Professor (later Corresponding Member of the Academy of Sciences) Pavel Andreevich Lehr, he successfully defended his candidate dissertation on the topic “Fauna and ecology of orthopteroid insects (Orthoptera) in the south of the Russian Far East”.